Successful resolution of hyperammonemia following hematopoietic cell transplantation with directed treatment of Ureaplasma parvum infection. Issue 2 (12th February 2018) - Graetz, Riley; Meyer, Robyn; Shehab, Kareem; Katsanis, Emmanuel
Abstract: Hyperammonemia following hematopoietic cell transplantation (HCT) has been characterized as idiopathic and is associated with a very high mortality. A causal relationship between Ureaplasma infection and hyperammonemia in immunocompromised lung transplant recipients has recently been described. We document the first case of hyperammonemia following HCT associated with Ureaplasma parvum . The initiation of appropriate antibiotics resulted in rapid resolution of hyperammonemic encephalopathy and eradication of the implicating organism.